Meningkatkan Kesadaran Digital Anak Sekolah Dasar terhadap Cyberbullying Dengan Metode Storytelling di RPTRA Anggrek Bintaro - Bazigha, Kahila; Hidayat, Nadira Nasywa; Nabighah, Najma; Amalia, Nabilla; Azizah, Nur (Jurnal Pustaka Dianmas, 2025)
Cyberbullying increasingly threatens digital awareness among young children in the digital era. This study aims to enhance digital awareness of 15 elementary school students (grades 1-5) at RPTRA Anggrek Bintaro regarding the dangers and impacts of cyberbullying, while equipping them with prevention and reporting skills. The primary approach employs interactive storytelling tailored for young children, featuring simple narratives, engaging visuals, and participatory elements to ensure material comprehension and empathy building. The outreach activity was conducted in a single 60-minute session, involving storytelling on identifying cyberbullying behaviors (online insults and rumor spreading), emotional impacts on victims (anxiety and social isolation), and prevention steps (ignore, block, and report to adults). This method is grounded in constructivist learning theory, where children actively construct understanding through interaction. Observation results indicate that 87% of participants (13 out of 15 children) actively engaged, successfully identified cyberbullying actions in the stories (average comprehension score of 85% via post-activity quiz), and demonstrated increased empathy toward victims. No significant confusion was observed regarding prevention materials. The impact fosters early digital awareness, reduces future risks of becoming perpetrators or victims of cyberbullying, and strengthens RPTRA's role as a supportive community for digital literacy. This study recommends replication in similar educational institutions to support preventive education paradigms in Indonesia.